Generation of Transgenic Energy Cane Plants with Integration of Minimal Transgene Expression Cassette - M. Fouad, Walid; Hao, Wu; Xiong, Yuan; Steeves, Cody; K. Sandhu, Surinder; Altpeter, Fredy (Current Pharmaceutical Biotechnology, 2015)
Lignocellulosic biomass has the potential to serve as feedstock and direct replacement for petrochemicals in the fuel, chemical, pharmaceutical and material industries. Energy cane has been identified by the U.S. Department of Energy (DOE) as prime lignocellulosic feedstock as it produces record biomass yields and is able to grow on low-value land with reduced inputs. Molecular improvement of energy cane is an essential step toward the development of a high-value crop and may contribute to improved biomass conversion to value added products. Such improvements require a development of an efficient regeneration and transformation system for the vegetatively propagated energy cane varieties. In this report, an efficient biolistic gene delivery protocol for energy canes (genotype L 79-1002 and Ho 00-961) has been established with immature leaf rolls as explants. Embryonic calli, developed approximately 6 weeks after culture initiation and was used as target for biolistic transfer of a minimum expression cassette of P-ubi::nptII::35S polyA derived from plasmid pJFNPTII. Putative transgenic clones of callus were obtained after selection on callus induction medium supplemented with 30 mg l-1 geneticin. Regeneration was carried out on NB medium, which is modified from MS supplemented with 1.86 mg l-1 naphthaleneacetic acid (NAA) and 0.1mg l-1, 6- benzylaminopurine (BAP) and 20mg l-1 paromomycin. Shoots growing on selection media were transferred to hormone free medium with 20 mg l-1 paromomycin. Putative transgenic lines were first analyzed by PCR. Transgene integration was confirmed by Southern blot analysis. ELISA (Enzyme-Linked Immunosorbent Assay) and Immunochromathography assays confirmed transgene expression.
Keywords: particle bombardment